Allopolyploid Origin of Chenopodium album s. str. (Chenopodiaceae): A Molecular and Cytogenetic Insight. - Karol Krak; Petr Vít; Alexander Belyayev; Jan Douda; Lucia Hreusová; Bohumil Mandák (PLoS ONE, 2016)
Reticulate evolution is characterized by occasional hybridization between two species, creating a network of closely related taxa below and at the species level. In the present research, we aimed to verify the hypothesis of the allopolyploid origin of hexaploid C. album s. str., identify its putative parents and estimate the frequency of allopolyploidization events. We sampled 122 individuals of the C. album aggregate, covering most of its distribution range in Eurasia. Our samples included putative progenitors of C. album s. str. of both ploidy levels, i.e. diploids (C. ficifolium, C. suecicum) and tetraploids (C. striatiforme, C. strictum). To fulfil these objectives, we analysed sequence variation in the nrDNA ITS region and the rpl32-trnL intergenic spacer of cpDNA and performed genomic in-situ hybridization (GISH). Our study confirms the allohexaploid origin of C. album s. str. Analysis of cpDNA revealed tetraploids as the maternal species. In most accessions of hexaploid C. album s. str., ITS sequences were completely or nearly completely homogenized towards the tetraploid maternal ribotype; a tetraploid species therefore served as one genome donor. GISH revealed a strong hybridization signal on the same eighteen chromosomes of C. album s. str. with both diploid species C. ficifolium and C. suecicum. The second genome donor was therefore a diploid species. Moreover, some individuals with completely unhomogenized ITS sequences were found. Thus, hexaploid individuals of C. album s. str. with ITS sequences homogenized to different degrees may represent hybrids of different ages. This proves the existence of at least two different allopolyploid lineages, indicating a polyphyletic origin of C. album s. str.